Computational Evaluation of Drug-Likeness and ADME Properties of Pyrazole and Chalcone Derivatives (Journal of Advances and Scholarly Researches in Allied Education, 2026)
The pyrazole and chalcone derivatives are bioactive molecules that have considerable therapeutic importance. In this study, 16 derivatives were computationally studied using the software of Molinspiration, admetSAR, AI Drug Lab, and vNN-ADMET to analyze their physicochemical properties, druglikeness, and ADMET properties. The Lipinski Rule of Five, along with other druglike filters, was used to screen compounds and identify potential oral medications. Based on the analysis of these compounds compared to curcumin, which acted as the reference molecule, a few compounds exhibited better absorption, permeability, oral bioavailability, and metabolic stability. The toxicity analysis also predicted good safety profiles for these molecules. Compound 11 emerged as the compound with the best balance of pharmacokinetics and toxicity among the studied compounds.